Comparative transcriptome analysis of mixed tissues of black porgy (Acanthopagrus schlegelii) with differing growth rates. (15th July 2021) - Lin, Zhijie; Zhang, Zhiyong; Solberg, Monica Favnebøe; Chen, Ziqiang; Wei, Mingliang; Zhu, Fei; Jia, Chaofeng; Meng, Qian; Zhang, Zhiwei
Abstract: In order to explore the main regulatory genes and pathways of growth traits in black porgy, Illumina high‐throughput sequencing technology was used to perform transcriptome sequencing of mixed samples of brain, liver and muscle tissues of 4‐month‐old black porgy individuals with different growth rates, followed by bioinformatics analyses. Using GO (Gene Ontology) function enrichment analysis and KEGG (Kyoto Encyclopedia of Genes and Genomes) Pathway analysis, relevant regulatory pathways involved in the process of muscle growth and material metabolism of black porgy were found. In order to compare differentially expressed genes of fast‐growing and slow‐growing groups of black porgy, a total of 3104 DEGs were screened, of which 1129 were up‐regulated genes and 1975 were down‐regulated genes, including myosin heavy chain (MYH4), IGF‐1, IGF‐2, myosin light chain 3‐like (Myl3), myosin‐6‐like (MYH6), myoglobin (Mb), growth hormone receptor type 1 (GHR1), and other key genes involved in the regulation of muscle growth. Through GO and KEGG enrichment analysis, we found 25 significantly enriched GO entries and 39 KEGG pathways related to growth, such as metabolic pathways, thyroid signalling pathways and PPAR signalling pathways. These differential genes and signalling pathways may play a key role in regulating growth of black porgy and provide a theoretical basis for further exploration of the key molecular mechanisms regulating growth and development of black porgy, ultimately contributing to the development of unique breeding strains of this species.